Women’s Language Used By Characters In “Brave” Movie - Ananda Sinta Ramadina; Ni Luh Nyoman Seri Malini; Ni Luh Putu Krisnawati (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Abstract: The title of this research is women’s language used by the characters in Brave movie. It aims to analyze the types of female language used by the characters in Brave movie. The data source is taken from the Brave movie script. The data was collected by reading the movie script and choosing which part contains women’s language in movie "Brave" script. The qualitative descriptive method is used in analyzing it using the theory of Lakoff (1975). The results showed that 5 types of 9 women's languages were found in the Brave movie script. They are intensifiers, rising intonation, emphatic stress, lexical hedges, and super polite form.